Significant PTSD and Other Mental Health Effects Present 18 Months After the Fort Mcmurray Wildfire: Findings From 3,070 Grades 7–12 Students - Brown, Matthew R. G.; Agyapong, Vincent; Greenshaw, Andrew J.; Cribben, Ivor; Brett-MacLean, Pamela; Drolet, Julie; McDonald-Harker, Caroline; Omeje, Joy; Mankowsi, Monica; Noble, Shannon; Kitching, Deborah T.; Silverstone, Peter H. (Frontiers in Psychiatry, 2019)
Background: The May 2016 wildfire in Fort McMurray, Alberta, Canada forced evacuation of the population of 88,000 individuals and destroyed 10% of the homes. Youth are particularly impacted by disaster. Methods: 18 months after the wildfire, Fort McMurray Public and Catholic Schools surveyed 3,252 of the 4,407 students in Grade 7-12 to determine possible long-term psychological impacts. The survey included validated measurement scales for post-traumatic stress disorder (PTSD), depression, anxiety, use of drugs, alcohol, and tobacco, quality of life, self-esteem, and resilience. Data analysis was only possible for 3,070, i.e. 70% of the total student population. Anonymized data were analyzed to compare students who directly experienced lesser or greater impact from the wildfire, with greater impact defined as personally seeing the fire or having ones home destroyed. Also, students with greater or lesser scores on the Child and Youth Resilience Measure (CYRM-12) were compared. Results: Of the 3,070 students, 37% met criteria for probable PTSD. 31% met criteria for probable depression, and 17% for probable depression of at least moderate severity. 27% of students met criteria for probable anxiety, and 15% for probable alcohol or substance use disorder. 46% of all students met criteria for one or more probable diagnosis of PTSD, depression, anxiety, or alcohol / substance abuse, and this included students who were both present and not present in Fort McMurray at the time of the wildfire. Students with greater impact from the wildfire exhibited significantly higher scores on measures of PTSD, depression, anxiety, and alcohol / substance use. They also had lower self-esteem and quality of life scores. Students with lower resilience scores exhibited a similar pattern. Conclusions: These findings highlight first the negative impact of disasters on youth mental health, particularly for those who directly experience wildfire, and second the role of resilience on youth mental health, with lower resilience associated with substantially lower mental health outcomes. These findings emphasize the need for long-term mental health supports for youth post-disaster, with specific focus on increasing youth resilience, which may serve as a protective factor against effects of disaster on mental health.